A SIMPLE METHOD FOR Cu, Zn AND Mo PURIFICATION AND MASS BIAS CORRECTION FOR PRECISE AND ACCURATE ISOTOPIC RATIO DETERMINATION IN GEOLOGICAL SAMPLES BY MC-ICPMS - Guedes, Suzana de Souza; Bellotto, Valéria Regina; Santos, Roberto Ventura; Dantas, Elton Luiz (Geochimica Brasiliensis, 2019)
A simple and quick method for simultaneous purification of Cu, Zn and Mo and accurate and precise measurement of their isotopic composition in geological samples using multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) has been developed. The method involves the use of a single chromatographic column filled with the anion exchange resin AG-MP-1 for complex matrix removal and further purification of these three elements. The external standard-sample-standard bracketing (SSB) procedure combined to internal standard addition was used for accurate mass bias correction and precise Cu, Zn and Mo isotopic ratio measurements. The method was applied to different geological materials, as granodiorite (GSP 2-USGS), limestone (JLS-1, Japan), Buffalo River Sediments (NIST SRM - 8704) and sediments from Amazon River Basin. The mean precision for these samples was: 0.08 ‰ for δ65/63Cu; 0.05 ‰ for δ66/67Zn and 0.04 ‰ for δ98/95Mo. The main advantage is that the proposed method is simple and rapid, and carries out the quantitative recovery of elements of different atomic masses and at very low concentration ranges, mainly for Mo. In addition, optimizations made the calibration and correction of instrumental mass bias easier, leading to consistent results with other methods that are currently published. The comparison of isotopic compositions of Cu and Mo obtained for granodiorite with respect to data reported in the literature demonstrate that the simpler and multi-element method developed in this study can be properly used within the required limits of accuracy as a multi-proxy tool in isotope geochemistry.